Correlation of left ventricular myocardial work indices with invasive measurement of stroke work in patients with advanced heart failure - Landra, Federico; Mandoli, Giulia Elena; Chiantini, Benedetta; Barilli, Maria; Merello, Giacomo; De Carli, Giuseppe; Sciaccaluga, Carlotta; Lisi, Matteo; Flamigni, Filippo; D’Ascenzi, Flavio; Focardi, Marta; Fineschi, Massimo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: This study aimed to explore the correlation between left ventricular (LV) myocardial work (MW) indices and invasively-derived LV stroke work index (SWI) in a cohort of patients with advanced heart failure (AHF) considered for heart transplantation. Background: LV MW has emerged as a promising tool for diagnostic and prognostic purposes in heart failure (HF) but its relationship with hemodynamic data derived from right heart catheterization (RHC) has not been assessed in patients with advanced heart failure yet. Methods: Consecutive patients with AHF considered for heart transplantation from 2016 to 2021 performing RHC and echocardiography as part of the workup were included. Conventional LV functional parameters and LV MW indices, including LV global work index (GWI), LV global constructive work (GCW), LV global wasted work (GWW), LV global work efficiency (GWE) and other were calculated and compared with invasively-measured LV SWI. Results: The population included 44 patients. Median time between RHC and echocardiography was 0 days (IQR: 0 – 24). Median age was 60 years (IQR: 54–63). For the most part, etiology of HF was non-ischemic (61.4%) and all patients were either on class NYHA II (61.4%) or III (27.3%). Median left ventricular ejection fraction was 25% (IQR: 22.3–32.3), median NT-proBNP 1377 pg/mL (IQR: 646–2570). LV global longitudinal strain (GLS) significantly correlated with LV SWI (r=-0.337; p=0.031), whereas LV ejection fraction (EF) did not (r=0.308; p=0.050). With regard to LV MW indices, some of them demonstrated correlation with LV SWI, particularly LV GWI (r=0.425; p=0.006), LV GCW (r=0.506; p=0.001), LV global positive work (LV GPW; r=0.464; p=0.003) and LV global systolic constructive work (GSCW; r=0.471; p=0.002). Conclusions: Among LV MW indices, LV GCW correlated better with invasively-derived SWI, potentially representing a powerful tool for a more comprehensive evaluation of myocardial function.